Finite element analysis on post-buckling of thin-walled structures using ANSYS - Muhammad Bathusha Maideen. (2012)
This project aims to develop a standard design procedure to simulate the buckling and post-buckling behaviour of thin-walled structures using finite element analysis, and hence determining a conservative estimate of the ultimate compressive load. The finite element program ANSYS (academic version 13.0) was utilized for the purpose of this study. This report is a continuation of previous studies under the same name, and documents the design procedure that was developed as well as new improvements made to it.